Soil mineral nitrogen dynamics in fallow periods in a rainfed semiarid Mediterranean agricultural system - SHAKOOR, Awais; BOSCH-SERRA, Àngela D.; LIDON, Antonio; GINESTAR, Damián; BOIXADERA, Jaime (Pedosphere, 2023)
Rainfed agricultural systems in semiarid Mediterranean environments are subject to erratic but often heavy rainfall events. As an agronomic practice, fallow periods can be included even within the existing European Union common policy for crop diversification. This study aimed to quantify the effects of previous mineral fertilization on soil mineral nitrogen (Nₘᵢₙ) content and potential nitrate leaching during no-till fallow periods of crop rotation. The Leaching Estimation and Chemistry Model (LEACHM) was used for soil Nₘᵢₙ prediction after fallow. During fallow periods, Nₘᵢₙ measured in the soil profile increased by an average of 125 kg N ha⁻¹, whereas the model showed an average increase of 95 kg N ha⁻¹. The amount of nitrogen (N) leached was estimated to be 11–38 kg N ha⁻¹. The N balance simulated using LEACHM might differ from the actual situation. The calibrated LEACHM underestimated soil Nₘᵢₙ after a drought period followed by soil water replenishment, probably due to a pulse in soil C and N mineralization caused by the wetting of dry soil, but overestimated soil Nₘᵢₙ after occasional rainy spells when soil quickly became saturated, probably due to occasional nitrous oxide emissions not being fully accounted for by the model and specific preferential water flow, which might lead to greater nitrate leaching than that simulated by LEACHM using the convection-dispersion equation. The results show that soil Nₘᵢₙ measurements after fallow periods cannot be well predicted by LEACHM. The findings of this study provide a support for fertilization planning for crop rotation systems including a fallow period to avoid overfertilization in the following cropping season and reduce N environmental impacts.